Properties of constitutional principles - S. A. Mosin (Правоприменение)
The subject. The article is devoted to the study of the trinity of properties of constitutional principles.The purpose of the article is to confirm the hypothesis that constitutional principles, often perceived by researchers and law enforcement officials as abstract norms with declarative content, are in fact full-fledged legal institutions that are endowed with all the necessary properties to achieve constitutional goals. In this regard, the article analyzes the property of axiomaticity, the property of presumptivity and the property of fictitiousness of constitutional principles.The methodology. The systemic-structural, comparative, formal-legal and formal-logical methods made it possible to identify and characterize the properties of constitutional principles, such as axiomaticity, presumptivity and fictitiousness. The use of these methods in their combination predetermined the appeal not only to topical problems of constitutional law, but also to issues of the theory of law, as well as other branches of law, which made it possible to most objectively and comprehensively approach the study of the properties of constitutional principles.The main results of the research. The trinity of the properties of the constitutional principle lies in the fact that the constitutional principle formulates the basic rule and determines the direction of development of the legal system and thereby has the property of axiomaticity. At the same time, the constitutional principle has the property of presumptivity due to the duty of the law enforcement officer to proceed from the assumption of compliance with the provisions of such a principle by all subjects of legal relations. Thereby constitutional principle ensures the necessary stability of the legal system of the state. At the same time, in order to achieve full-fledged stability of the legal system, along with the assumption that the subjects of legal relations comply with the provisions of the constitutional principles, it should be possible to monitor such compliance. In the absence of prior control over compliance with the provisions of the law, the solution is the application of legal presumptions. In this regard, within the framework of the presumptive property of constitutional principles, constitutional presumptions are inextricably linked with the corresponding constitutional principles. In turn, having the property of fictitiousness, the constitutional principle allows to interpret the provisions that make up such a constitutional principle and, as a result, create the necessary regulatory legal framework.Conclusions. Constitutional principles are the driving force of the legal system. They fill all legal relations without exception with legal meaning and content and have a special meaning due to their irreplaceability and the obligation to strictly observe them. In turn, the trinity of properties of the constitutional principles reflects their legal essence as fundamental normative provisions that determine the generally binding basic rules and directions of the development of the legal system, ensure the stability of the legal system of the state, and also have the possibility of timely development and adaptation to the changing legal reality.